HUBUNGAN ANTARA KARAKTERISTIK DENGAN TINGKAT KECEMASAN PASIEN KONFIRMASI COVID-19 YANG MENJALANI ISOLASI MANDIRI DI WILAYAH UPT PUSKESMAS KARANGMOJO I - Khoeriyah, Salis Miftahul (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2022)
Background: The Covid-19 pandemic has become a health crisis in the world because it spreads very quickly, this can cause anxiety in the community, one of which is Covid-19 confirmed patients who are undergoing independent isolation. The level of anxiety is influenced by many factors, both internal and external. undergoing self-isolation at UPT Puskesmas Karangmojo I. Objective: to find out whether there is a relationship between patient characteristics and the anxiety level of Covid-19 confirmed patients Method: correlation with cross-sectional approach. . The number of samples in this study were 42 people with total sampling technique. Data was collected using the HRS-A 14 (Hamilton Rating Scale for Anxiety) questionnaire via google form. Result: 64% of patients who underwent self-isolation experienced anxiety with mild anxiety levels, 19.0% with moderate anxiety levels, 9.5% with severe anxiety levels and 7.1% did not experience anxiety. Factors related to the level of anxiety is the level of education with the Asymp value. Significance 0.017<0.05 and age with Asymp value. Significance 0.018<0.05. Conclusion: most of the confirmed Covid-19 patients who underwent independent isolation at the Karangmojo I Public Health Center experienced anxiety with a mild level of anxiety, and there was a relationship between patient characteristics and the patient's level of anxiety. Characteristics of respondents related to the level of anxiety is the level of education and age of the respondent.